“Junk You Can't Abandon”: Hoarding and Waste in Andrew Lam and Karen Tei Yamashita - Simal-González, Begoña (International Journal of English Studies, 2022)
In the last decades a concern with waste has started to “surface” not just in the economic and social sciences, but also in the humanities, where it has lately clustered around Waste Studies and Waste Theory. This critical approach allows us to grapple with the consequences of our globalized economy of waste for both the planet and human beings. Although Waste Theory can be applied to virtually any literary tradition, I would argue that Asian American literature, which has been read along the lines of the waste/no-waste dialectics since Sau-ling Wong developed her Necessity/Extravagance thesis in 1993, proves particularly amenable to this methodology. In order to illustrate the multiple ways in which Waste Theory can productively interbreed with Wong’s dichotomy, I will explore the dynamics of hoarding and waste in Andrew Lam’s Perfume Dreams and Karen Tei Yamashita’s Sansei and Sensibility.